2021
DOI: 10.3389/fneur.2021.655434
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Care During the First and the Second Waves of the COVID-19 Pandemic in a Community Hospital

Abstract: Objective: The coronavirus disease 2019 (COVID-19) infection may alter a stroke course; thus, we compared stroke course during subsequent pandemic waves in a stroke unit (SU) from a hospital located in a rural area.Methods: A retrospective study included all patients consecutively admitted to the SU between March 15 and May 31, 2020 (“first wave”), and between September 15 and November 30, 2020 (“second wave”). We compared demographic and clinical data, treatments, and outcomes of patients between the first an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In addition, a multicenter study conducted in Germany showed that the number of stroke admissions decreased during the COVID-19 outbreak, whereas the rate of acute reperfusion therapy was not significantly affected [24]. In contrast, Sobolewski et al [25] reported that the reperfusion procedure increased as the stroke with large vessel occlusion increased during the second wave of the COVID-19 pandemic in Poland. The present study did not show these reductions reported in previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, a multicenter study conducted in Germany showed that the number of stroke admissions decreased during the COVID-19 outbreak, whereas the rate of acute reperfusion therapy was not significantly affected [24]. In contrast, Sobolewski et al [25] reported that the reperfusion procedure increased as the stroke with large vessel occlusion increased during the second wave of the COVID-19 pandemic in Poland. The present study did not show these reductions reported in previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…As is seen across all types of strokes, COVID-19 infection is associated with poorer prognosis in patients with an LVO [ 19 ]. A study by Ntaios et al found that through their propensity score-matched analysis of COVID-19 patients compared to non-COVID-19 patients registered in the Acute Stroke Registry and Analysis of Lausanne Registry between 2003 and 2019, the median National Institutes of Health Stroke scale score was found to be higher in patients with COVID-19 compared to patients without COVID-19 (10 (interquartile range (IQR): 4-18) and six (IQR: 3-14), p = 0.03) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%